Targeting extracellular glycans: tuning multimeric boronic acids for pathogen-selective killing of Mycobacterium tuberculosis. Issue 23 (16th May 2019) - Guy, Collette S.; Gibson, Matthew I.; Fullam, Elizabeth
Abstract : Innovative chemotherapeutic agents that are active against Mycobacterium tuberculosis ( Mtb ) are urgently required to control the tuberculosis (TB) epidemic. Abstract : Innovative chemotherapeutic agents that are active against Mycobacterium tuberculosis ( Mtb ) are urgently required to control the tuberculosis (TB) epidemic. The Mtb cell envelope has distinct (lipo)polysaccharides and glycolipids that play a critical role in Mtb survival and pathogenesis and disruption of pathways involved in the assembly of the Mtb cell envelope are the primary target of anti-tubercular agents. Here we introduce a previously unexplored approach whereby chemical agents directly target the extracellular glycans within the unique Mtb cell envelope, rather than the intracellular biosynthetic machinery. We designed and synthesised multimeric boronic acids that are selectively lethal to Mtb and function by targeting these structurally unique and essential Mtb cell envelope glycans. By tuning the number of, and distance between, boronic acid units high selectivity to Mtb, low cytotoxicity against mammalian cells and no observable resistance was achieved. This non-conventional approach may prevent the development of drug-resistance and will act as a platform for the design of improved, pathogen-specific, next generation antibiotics.